Azerbaijani youth in transition: Is the state youth policy effective enough?. Issue 2 (July 2021) - Valiyev, Anar; Babayev, Abbas
This article analyzes the role of the state youth policy of Azerbaijan in supporting young people through their transition from school to work, which is one of the stages when young people can be in particularly fragile situation if not provided with necessary opportunities. The reason for studying the case of Azerbaijan is a considerable share of youth Not in Employment, Education, or Training (NEET youth) among the country's youth community. The NEET indicator is considered as a comprehensive indicator within the post-2015 Sustainable Development Agenda to measure youth exclusion and marginalization. The findings of this research demonstrate that while the government assumes a broad responsibility to provide youth with education and employment opportunities to support their transition, these intentions have not been translated into real actions. An alarming situation of the country's youth population is at risk of further exacerbation due to poor understanding of local realities by such global advocates for youth development as United Nations. We discuss this considering the flaws in the operationalization and localization of the concept of the "youth participation" promoted by the United Nations to advance youth interests.